Faith-based organizations at the United Nations - Haynes, Jeffrey (Palgrave studies in religion, politics, and policy, 2014)
"The book examines selected faith-based organisations (FBOs) and their attempts to seek to influence debate and decision-making at the United Nations (UN). Increasing attention on FBOs in this context has followed what is widely understood as a widespread, post-Cold War 'religious resurgence', which characterises a novel 'postsecular' international environment. One aspect of the new postsecular environment is increasing focus on global public policy at the UN, from FBOs from various religious traditions, especially Christianity, Islam, and Judaism"--